Kajian Vegetasi Sebagai Peredam Kebisingan Yang Ditimbulkan Oleh Kereta Api Di Kecamatan Gamping, Kabupaten Sleman, D.I. Yogyakarta - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2002)
ABSTRACT The train makes alot of noise that disturbes the people in the form of noise pollution. The aim of this research was to investigate the effect of the plant to eliminate the noise in Gamping, Sleman, D.1. Yogyakarta.The research was done by divided the study area. in 10 plots (10 m x 30 m) and each plot was divided into 3 sub plots. The plant in each sub plot was collected in order to determine the species and the plant parameter was measured. The level of the noise was measured by sound level meter at the distance of 10 m, 20 m, and 30 m from the railroad. The results of the research showed that the plant can eliminate the noise level ranging from 0,2 up to 6,0 dB(A). Based on the multiple regression analysis by backward model, it can be observed that the biggest contribution of plant parameter on the level of noise elimination was at 30 meters from the source of noise. The contribution was 58,4 %. Moreover, the crucial factor to eliminate the noise is the average of the stem hight and the average of canopy width.